Mitoxantrone Hydrochloride Liposome Combined with Cytarabine As Induction Therapy for Patients with Newly Diagnosed Secondary Acute Myeloid Leukemia - Wang, Yun; Wang, Weida; Xu, Jingbo; Ma, Ji; Wang, Hua; Wu, Bingyi; Song, Yuanbin; Lv, Weiran; Chen, Lezong; Ma, Jun; Gong, Tiejun; Liang, Yang (Blood, 2024)
Background: Secondary acute myeloid leukemia (sAML) is an aggressive subset of acute myeloid leukemia (AML). sAML is more prevalent in older patients (pts) and is associated with adverse biological features, as well as a multi-drug resistance phenotype that contributes to the limited efficacy of conventional induction therapies. Although newly approved drugs and regimens, such as CPX-351 and venetoclax combined with hypomethylating agents (HMAs), have shown promising efficacy in sAML-with composite complete remission (CRc) rates ranging from 48% to 60%. However, the outcomes for pts with adverse-risk cytomolecular features are still suboptimal. Mitoxantrone has been shown to exhibit partial non-cross-resistance with anthracyclines. Mitoxantrone hydrochloride liposome (Lipo-MIT) is a pegylated liposomal formulation of mitoxantrone that offers enhanced efficacy and lower toxicity. We hypothesize that Lipo-MIT combined with cytarabine (MA) based regimens could demonstrate improved outcomes in newly diagnosed sAML pts. Methods: Data of adult pts with newly diagnosed sAML from an ongoing prospective study and a real-world study were collected. The definition of sAML was that AML pts with a history of myelodysplastic syndromes (MDS) or CMML, MDS-related cytogenetics, and/or exposure to prior chemotherapy or radiotherapy for another malignancy. Enrolled patients were required to have an Eastern Cooperative Oncology Group (ECOG) performance status of 2 or less. Patients received MA-based regimens consisted of Lipo-MIT and cytarabine with/without other drugs up to 2 cycles. Rate of CRc (complete remission (CR)+CR with incomplete neutrophil or platelet recovery (CRi)), CR/CRi with negative minimal residual disease (MRD), overall response rate (ORR), event-free survival (EFS), overall survival (OS) and safety were analyzed. Results: A total of 14 pts were enrolled, including 10 with therapy-related AML and 4 with AML arising from antecedent MDS. The median age was 56.5 years (range, 22.0-65.0). The French-American-British (FAB) subtypes were as follows: M1 in 2 pts (14.3%), M2 in 6 pts (42.9%), M5 in 5 pts (35.7%), and 1 patient (7.1%) without a specific subtype. According to the 2022 edition of the European Leukemia Network recommendations, 3 (21.4%) were classified as having a favorable prognosis, 3 (21.4%) as intermediate, 7 (50.0%) as adverse, and 1 (7.1%) as unknown. TP53 was the most commonly mutated gene identified in 25.0% of 12 pts who underwent molecular examination. Karyotype analysis was conducted in 12 pts, revealing abnormalities in 8 pts (66.7%), with the most frequent abnormality being del(7q) observed in 25.0%. Of 14 pts, 12 (85.7%) received MA regimen, 1 (7.1%) received MA+venetoclax (MAV) regimen and 1 (7.1%) received MA+granulocyte colony stimulating factor (G-CSF) regimen. Median dose of Lipo-MIT was 23.6 mg/m2 (range 12.0-26.0). As of the data cut-off on July 30, 2024, the CRc rate was 64.3% (9/14) and the ORR was 71.4% (10/14). Among 4 pts who did not achieve ORR, 2 pts had a reduction in bone marrow blasts of more than 50%. Patients classified as favorable/intermediate risk had a higher CRc of 83.3% (5/6) while adverse group was 42.9% (3/7). Additionally, among 9 pts achieving CR/CRi, flow cytometry were available for 7 pts, revealing a rate of negative MRD of 85.7% (6/7). At a median follow-up time of 4.68 months (range, 1.1-28.7), 4 pts occurred treatment failure, 1 patient died and 2 pts loss of follow-up. The median EFS and OS were not reached. Among pts achieving remission in cycle 1, the median duration of absolute neutrophil count <1000 cells/μL was 21.0 days (range, 12.0-31.0) and platelet count <25000 platelets/μL was 12.0 days (range, 6.0-41.0). The most common non-hematological treatment-emergent adverse events graded at 3 were fever (21.4%), sepsis (14.3%), pulmonary infection (7.1%), anaphylaxis (7.1%) and pruritus (7.1%). No adverse events of grade 4 or worse were observed and the mortality rate of 60-day was 0%. Conclusions: Lipo-MIT combined with cytarabine-based regimens achieved encouraging rates of CRc and MRD negativity in newly diagnosed sAML with a well tolerated safety profile. Larger sample size and prolonged follow-up time are needed. No relevant conflicts of interest to declare. Mitoxantrone hydrochloride liposome is an anthracycline anti-tumor drug approved by the National Medical Products Administration (NMPA) for the treatment of relapsed or refractory Peripheral T-cell Lymphoma patients who have previously undergone at least one line of therapy.